1987
DOI: 10.1002/ajmg.1320280535
|View full text |Cite
|
Sign up to set email alerts
|

Chronic renal failure and XY gonadal dysgenesis: “Frasier” syndrome—a commentary on reported cases

Abstract: The development of chronic renal failure because of parenchymatous renal disease in patients in 46,XY gonadal dysgenesis was noted initially by Drash et al [J Pediatr 76:585–593,1970]. However, we think that some of the cases reported as examples of the Drash syndrome are a different disorder. In this paper, we review six previously reported patients with streak gonads, pseudohermaphroditism, and renal failure. In several of these patients the diagnosis was established only after a successful kidney transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…In Denys-Drash syndrome, characterized by the association of early-onset glomerulopathy with diffuse mesangial sclerosis, gonadal dysgenesis leading to pseudohermaphroditism in males, and a high risk of developing Wilms' tumor (40 -42), dominant negative point mutations affect the zinc fingers of the WT1 protein and, consequently, its binding to DNA (43) and result in abnormal podocyte expression of PAX2 and growth factors PDGF and TGF-␤1 (44). Mutations are different in Frasier syndrome, characterized by male pseudohermaphroditism with complete sex reversal and streak gonads frequently at the origin of gonadoblastomas, associated with slowly progressive glomerulopathy (45). They are intronic mutations in the second splicing site of the gene (46).…”
Section: Denys-drash and Frasier Syndromesmentioning
confidence: 99%
“…In Denys-Drash syndrome, characterized by the association of early-onset glomerulopathy with diffuse mesangial sclerosis, gonadal dysgenesis leading to pseudohermaphroditism in males, and a high risk of developing Wilms' tumor (40 -42), dominant negative point mutations affect the zinc fingers of the WT1 protein and, consequently, its binding to DNA (43) and result in abnormal podocyte expression of PAX2 and growth factors PDGF and TGF-␤1 (44). Mutations are different in Frasier syndrome, characterized by male pseudohermaphroditism with complete sex reversal and streak gonads frequently at the origin of gonadoblastomas, associated with slowly progressive glomerulopathy (45). They are intronic mutations in the second splicing site of the gene (46).…”
Section: Denys-drash and Frasier Syndromesmentioning
confidence: 99%
“…In 1964, Frasier et al reported phenotypic female identical twins with XY gonadal dysgenesis with streak gonads, gonadoblastoma, and chronic kidney failure [7]. Similar patients were subsequently described, and in 1987 Moorthy et al collected 6 patients and proposed that these symptoms should be called Frasier syndrome (FS) [8]. FS is caused by mutation in the WT1 gene, which is located on chromosome 11p13.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, in the podocytes of DDS patients, WT1 mutants result in overexpression of Pax-2, which should be repressed after early nephrogenesis [110]. Second, mutations in the donor splice site at intron 9 lead to Frasier syndrome (FS), which is described as a combination of complete XY gonadal dysgenesis, FSGS and gonadoblastoma in 46, XY patients and as nephropathy alone in 46, XX patients [121]. The third nephropathy is isolated SRNS.…”
Section: Wt1 Mutationsmentioning
confidence: 99%